Access to Cleaning Services Alters Fish Physiology Under Parasite Infection and Ocean Acidification - Paula, José Ricardo; Repolho, Tiago; Grutter, Alexandra S.; Rosa, Rui (Frontiers in Physiology, 2022)
Cleaning symbioses are key mutualistic interactions where cleaners remove ectoparasites and tissue from client fishes. Such interactions elicit beneficial effects on clients’ ecophysiology, with cascading effects on fish diversity and abundance. Ocean acidification (OA), resulting from increasing CO2 concentrations, can affect the behaviour of cleaner fishes making them less motivated to inspect their clients. This is especially important as gnathiid fish ectoparasites are tolerant to ocean acidification. Here, we investigated how access to cleaning services, performed by the cleaner wrasse Labroides dimidiatus, affects individual client’s (damselfish, Pomacentrus amboinensis) aerobic metabolism in response to both experimental parasite infection and OA. Access to cleaning services was modulated using a long-term removal experiment where cleaner wrasses were consistently removed from patch reefs around Lizard Island (Australia) for 17 years or left undisturbed. Only damselfish with access to cleaning stations had a negative metabolic response to parasite infection (maximum metabolic rate - ṀO2Max; and both factorial and absolute aerobic scope). Moreover, after an acclimation period of days to high CO2 ( 1000 µatm CO2), fish showed a decrease in factorial aerobic scope, being the lowest in fish without access to cleaners. We propose that stronger positive selection for parasite tolerance might be present in reef fishes without access to cleaners, but this might come at a cost, as readiness to deal with parasites can impact their response to other stressors, such as OA.